An international consensus report on a new algorithm for the management of infant diarrhoea. (27th May 2016) - Lo Vecchio, Andrea; Vandenplas, Yvan; Benninga, Marc; Broekaert, Ilse; Falconer, Jackie; Gottrand, Frederic; Lifschitz, Carlos; Lionetti, Paolo; Orel, Rok; Papadopoulou, Alexandra; Ribes‐Koninckx, Carmen; Salvatore, Silvia; et al.
Abstract: Aim: Implementing international guidelines guarantees high standards of clinical care. A group of experts developed an algorithm to drive the management of common gastrointestinal symptoms in infancy by paediatricians and general practitioners. Methods: The algorithm started from the evidence‐based recommendations of the European Society of Gastroenterology, Hepatology and Nutrition and the European Society of Pediatric Infectious Diseases and an updated review of the literature. We used the structured quantitative method of nominal group technique to reach a consensus. Results: A practical algorithm for the management of infants with acute diarrhoea was designed based on the consensus reached for each statement. The management of an infant with acute diarrhoea should include a sequence of actions: (i) a semiquantitative estimate of infant dehydration through validated clinical scores, (ii) rehydration therapy and early refeeding with breast milk or regular formula and (iii) effective agents to reduce the severity and duration of the diarrhoea. Finally, in children with prolonged diarrhoea, the search for aetiology should include persistent infections or reinfections, cows' milk protein allergy and coeliac diseases. Lactose should always be withdrawn. Conclusion: This algorithm provides an evidence‐based sequence of interventions to optimise the management of infants with acute diarrhoea.